AYU apps empowers the teaching and learning of sustainability - Mat, Hamidah; Mohd Yusof C.A. (M), Asmazatul Yusfiziati; Mohamed Fadzil, Ainul Fazrina; Yusof, Muhammad Suffi; Awi, Md Shahnon; Mohamed Anuar, Raziah; Ramli, Rusfazila; A. Saiman, Savina (Universiti Teknologi MARA, Sarawak, 2023)
Today generations must be extremely competitive and competent in a wide variety of subjects in order to be successful in the twenty-first century. The proliferation of technology is the focus of the Education 4.0 initiative. Therefore, students of today need to embrace digital learning rather than just being taught via memorization exercises and rote learning. The purpose of this research is to investigate the ways in which the Akademi Youtuber application (AYU applications) assists students in developing their self-directed learning abilities and serves as a reference for both educators and parents. The survey method uses a sample of 202 students from West Malaysia to assess the effectiveness of the Academy Youtuber application that was developed. It was determined, on the basis of the degree of agreement among the stiudents (98.7 percent), that AYU applications is appropriate for the development of self-learning abilities and can be readily accessible by students, parents, and instructors.